2014
DOI: 10.1016/j.celrep.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

CTCF Haploinsufficiency Destabilizes DNA Methylation and Predisposes to Cancer

Abstract: SUMMARY Epigenetic alterations, particularly in DNA methylation, are ubiquitous in cancer, yet the molecular origins and the consequences of these alterations are poorly understood. The DNA binding protein CTCF regulates a diverse array of epigenetic processes and is frequently altered by hemizygous deletion or mutation in human cancer. To date, a causal role for CTCF in cancer has not been established. Here we show that Ctcf hemizygous knockout mice are markedly susceptible to spontaneous, radiation, and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
205
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(221 citation statements)
references
References 21 publications
9
205
0
Order By: Relevance
“…Kemp et al 25 observed that hemizygous loss of Ctcf destabilised DNA methylation at epigenetically variable CpGs in normal lung tissue of mice, and divergent CpGs from Ctcf +/− lungs were significantly shifted towards cytosine hypermethylation and showed increased variance in methylation. Furthermore, they found significant hypermethylation in Ctcf +/− samples that extended to ~2 kb regions surrounding divergent CpGs 25. The above findings are consistent with our findings, which showed that patients with a heterozygous CTCF deletion showed a higher methylation level genome-wide.…”
Section: Discussionmentioning
confidence: 99%
“…Kemp et al 25 observed that hemizygous loss of Ctcf destabilised DNA methylation at epigenetically variable CpGs in normal lung tissue of mice, and divergent CpGs from Ctcf +/− lungs were significantly shifted towards cytosine hypermethylation and showed increased variance in methylation. Furthermore, they found significant hypermethylation in Ctcf +/− samples that extended to ~2 kb regions surrounding divergent CpGs 25. The above findings are consistent with our findings, which showed that patients with a heterozygous CTCF deletion showed a higher methylation level genome-wide.…”
Section: Discussionmentioning
confidence: 99%
“…While Ctcf is a well-known insulator protein in mammals, 45 genome-wide studies have recently demonstrated that 20-25% of Ctcfbound sites are located within proximal promoter regions, 46 and enrichment of E2f binding motifs has been identified among Ctcf-bound regions in multiple cell types. 47,48 Furthermore, the chromatin regulatory function of Ctcf has recently been established as a tumor suppressive mechanism, 49 akin to pRb/E2f. These studies substantiate our discovery, and Figure 5 In NPCs, E2fs bind the TSS of genes that are transcriptionally active in neurogenic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Such tumor-specific regulation of CTCF-binding sites by methylation is known (27). It has even been shown that CTCF itself can regulate DNA methylation patterns and that cancerous or immortalized cells, when compared with normal cells, have a distinct CTCFbinding landscape in the genome (28), highlighting the complexity of methylation-related regulation, especially when addressed in a locus-specific manner.…”
Section: Pace4 Splicing Is Regulated By Intraexonic Dna Methylationmentioning
confidence: 99%